Isadora in Action Lynn Seymour talks about Ashton - Parry, Jann (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Lynn Seymour talking about Ashton. PALABRAS CLAVE: Frederick Ashton, Lynn Seymour, Five Brahms Waltzes in the Manner of Isadora Duncan, The Two Pigeons, A Month in the Country.
Dentro del apartado "Celebrating Frederick Ashton. 17 September 1904 - 19 August 1988".